Raman and Fluorescence Spectroscopy of CeO2, Er2O3, Nd2O3, Tm2O3, Yb2O3, La2O3, and Tb4O7 - Jianlan Cui; Gregory A. Hope (Journal of Spectroscopy)
To better understand and ascertain the mechanisms of flotation reagent interaction with rare earth (RE) minerals, it is necessary to determine the physical and chemical properties of the constituent components. Seven rare earth oxides (CeO2, Er2O3, Nd2O3, Tm2O3, Yb2O3, La2O3, and Tb4O7) that cover the rare earth elements (REEs) from light to heavy REEs have been investigated using Raman spectroscopy. Multiple laser sources (wavelengths of 325 nm, 442 nm, 514 nm, and 632.8 nm) for the Raman shift ranges from 100 cm−1 to 5000 cm−1 of these excitations were used for each individual rare earth oxide. Raman shifts and fluorescence emission have been identified. Theoretical energy levels for Er, Nd, and Yb were used for the interpretation of fluorescence emission. The experimental results showed good agreement with the theoretical calculation for Er2O3 and Nd2O3. Additional fluorescence emission was observed with Yb2O3 that did not fit the reported energy level diagram. Tb4O7 was observed undergoing laser induced changes during examination.